2017
DOI: 10.1159/000475815
|View full text |Cite
|
Sign up to set email alerts
|

Ex utero Intrapartum Treatment to Ventricular Pacing: A Novel Delivery Strategy for Complete Atrioventricular Block with Severe Bradycardia

Abstract: Fetuses with anti-SSA-mediated complete atrioventricular block (CAVB) are at high risk for perinatal death if they present at <20 weeks of gestation and develop ventricular rates of <55 beats per minute (bpm), cardiac dysfunction, or hydrops [Izmirly et al.: Circulation 2011;124:1927-1935; Jaeggi et al.: J Am Coll Cardiol 2002;39:130-137; Eliasson et al.: Circulation 2011;124:1919-1926]. After our experience with two such fetuses who died with pulseless electrical activity despite being paced within 30 min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…A temporary epicardial pacing wire was sutured into the RV through a subxyphoid approach. The umbilical cord was then clamped, and the patient was delivered immediately with a permanent pacemaker placed on the third day of life (Cuneo et al, ; Table ). Invasive surgical placement of fetal pacemakers comes with significant surgical and medical risks, but these studies encouragingly demonstrate that fetal pacing is possible.…”
Section: Historical Attempts At Fetal Pacingmentioning
confidence: 99%
“…A temporary epicardial pacing wire was sutured into the RV through a subxyphoid approach. The umbilical cord was then clamped, and the patient was delivered immediately with a permanent pacemaker placed on the third day of life (Cuneo et al, ; Table ). Invasive surgical placement of fetal pacemakers comes with significant surgical and medical risks, but these studies encouragingly demonstrate that fetal pacing is possible.…”
Section: Historical Attempts At Fetal Pacingmentioning
confidence: 99%
“…Subramanian et al 12 found that regional anaesthesia has been used; however, this may lead to increased maternal anxiety, and due to the high risk of blood loss, general anaesthetic is more appropriate. Epidural was used in some cases as a form of post-operative pain relief 12,15 . General anaesthetic allows for the use of inhalation agents which cause tocolysis, described by Braden et al 2 as complete uterine relaxation.…”
Section: The Proceduresmentioning
confidence: 99%
“…In addition to inhalational agents such as desflurane 2, 12 sevoflurane 1 and isoflurane 15 , nitroglycerine was reported by multiple authors as being used to maintain tocolysis 2,8,11,12 . Tocolytic agents may cause maternal hypotension, which in turn may interfere with the maintenance of placental circulation and fetal oxygenation 8 .…”
Section: The Proceduresmentioning
confidence: 99%
See 2 more Smart Citations